PERFORMANCE TESTING OF AN AUTOMATIC SNOW LEVELER. - Abele,Gunars (1964)
A modified Gurries Automatic Road Builder was tested at the Keweenaw Field Station, Houghton, Michigan and in Greenland to determine its feasibility for leveling snow and producing trafficable snow surfaces, such as roads and runways in deep snow areas. The unit, a tow-type, hydraulically controlled, automatic leveler, normally used for accurate, finish leveling in highway and airfield construction work, had been modified for use in snow. The initial performance test results were very satisfactory. A few minor modifications were required, which were performed before the completion of the initial tests. The final performance tests were conducted in Greenland and consisted of trail and runway improvement and maintenance work. It was determined that the Gurries Automatic Road Builder can be used quite effectively for snow road and trail improvement and maintenance, and is especially well suited for snow runway leveling. (Author)